Financial Performance of Construction, Property, and Trading Companies Based on Working Capital, Liquidity Ratio, and Profitability Ratio - Gracia Gabriella Hindradjaja (Advances in Civil Engineering and Sustainable Architecture, 2019)
An investor needs to do an analysis to choose the best investment. This decision should be carried out with the right calculation and analysis of the company's performance. This research evaluates financial performance of several companies based on their working capital, liquidity, and profitability. Profitability ratio indicates company’s ability to make a profit. Liquidity ratio indicates company’s ability to pay debt in due date condition. Working investment shows that working capital needed by the company. Profitability and liquidity of the company is determined by financial ratio. This research is focused on investigating financial performances of three types of companies, namely construction, developer, and trade industry. The results of the liquidity and profitability ratios show that developer companies has the best liquidity ratio compared to construction and trading companies. The results of calculation of working capital show that construction companies need the minimal working capital than the other companies.